The physical exam's role in determining dose-limiting toxicity prior to immunochemotherapy administration in lymphoma - Runge, John S; Brown, Anna B; Phillips, Tycel J; Kaminski, Mark S; Carty, Shannon A; Wilcox, Ryan A (Journal of oncology pharmacy practice, 2023)
The COVID-19 pandemic has introduced new challenges to healthcare access and delivery. It is critical to identify areas for innovation within oncologic clinical practice to maintain high quality care. We evaluated the potential utility of telemedicine initiatives for patients with lymphoma undergoing immunochemotherapy. We conducted a retrospective review of adult lymphoma patients receiving R-CHOP  +  /- R, R-ICE, R-GEMOX, and R-DHAP at our institution in the last three years (2017-2019) and identified cycles for which dose modifications were required. We reviewed 1290 total treatment cycles in 301 unique patients, 1102 cycles (85.4%) were R-CHOP  +  /- R, 105 (8.1%) were R-ICE, 71 (5.5%) were R-GEMOX, and 12 (0.9%) were R-DHAP. We identified that 144 cycles (11.2%) were subject to dosing adjustments. We retrospectively reviewed laboratory results, patient history, and/or physical exam findings that informed dose modifications. Of the 144 dose adjustments, 11% of cycles contained dose increases due to a well-tolerated previous dose noted in the clinical assessment. The remaining 128 modified cycles were dose reductions. Notably, only 7/128 dose reductions were based on physical exam findings alone, due solely to a change in patient body weight. As patients are routinely weighed immediately prior to chemotherapy administration, effectively no dose modifications (0/144) were exclusively based on abnormal physical exam finding during a pre-infusion assessment. These findings suggest that pre-infusion assessments may be amenable to virtual visits for lymphoma patients undergoing immunochemotherapy.